Category of Sacredness in the Discourse of the English Sermon (Theolinguistic Approach) - Kravchenko, Nina; Karpenko, Elena; Matiienko-Silnytska, Anna; Vasylieva, Olga (Տիգրան Մեծ)
The present paper deals with the investigation of the category of sacredness of the English religious preaching discourse, considered from the standpoint of theolinguistics. It has been proved that being a secondary form of sacred texts the text of the sermon demonstrates frequent use of sacral vocabulary of different groups: narrow conceptual and terminological vocabulary, which has religious sense and meanings, borrowings from sacred texts (the so-called biblicalisms), and vocabulary of everyday communication, which in the context of preaching becomes religious, and is included in the semantic field of religion on this basis. Different perception of the nature and ways to realize the sermon in the Anglican and Neo-Protestant churches is manifested in the peculiarities of the attitude towards the sacrality of the Word. The process of desacralization of the sermon, recorded in the Neo-Protestant sermons, occurs due to the contrasting use of sacred vocabulary in a stylistically reduced context, on the one hand, and the use of profane vocabulary to nominate sacred phenomena, on the other.
Keywords: Philosophy